Counter-intuitive policy against cocaine cartels (2010)
ABSTRACT: The coca far ming dynamics seems to partially follow the patterns of a long war against organized crime in Colombian. Since the early 80s, the cocaine market in the US and the rest of the world has been mainly supplied by Colombian cartels. Consequently, these illegal organizations have been tar geted by Colombian and American law en forcement agencies. Our work argues that such policy has had a counter-intuitive effect which contributes to increases coca farming and reductions in cocaine prices. This paper hypothesizes that such situation was the consequence of the way that drug cartels were dismantled – thus the Colombian paradox. The consequences of the war against cartels may be assessed with the support of a dynamic theor etical framework and SD. Effective policy may consider alternative actions before dismantling drug cartels.